Say it right with ya / Putri Farra Atiqa Mohd Zaki and Siti Zuraina Gafar@Abd Ghaffar - Mohd Zaki, Putri Farra Atiqa; Gafar@Abd Ghaffar, Siti Zuraina (Academy of Language Studies, 2023)
Pronunciation errors in certain English words have been imminent among Malaysians due to assimilation. This phenomenon could be seen in the daily conversations of university students. The creation of Say it Right with Ya revolves around correcting commonly mispronounced English words made by Malaysians, specifically university students through Instagram. Presently, social media has become a platform for students to gain new knowledge in an interactive manner, as opposed to the traditional way of only learning within their classrooms. Numerous social media platforms have been used by educators to teach students, including Instagram. A verbal interview was conducted to observe how university students pronounce certain English words and it was noted that most participants made pronunciation errors during the interview. Multiple feedback received also showed that many young people did not realise that they were mispronouncing certain words wrongly and the Instagram account created helped them to correct their mistakes. This research was able to conclude that correcting mispronunciation among students could be done using social media, namely Instagram.